Polish Forced Labourers in the Klaipėda Region during World War II - Chomej, Dawid (Genocidas ir rezistencija, 2024)
This paper examines the plight of Polish forced labourers in the Klaipėda region during World War II, shedding light on a lesser-known aspect of Nazi occupation policies. Drawing on a database maintained by the Polish Institute of National Remembrance, the author collected data on nearly 2,000 Polish individuals subjected to forced labour in Klaipėda. Through archival research and analysis of personal testimonies, the study explores the demographics, origins, working conditions, and treatment of these labourers.The occupation of Klaipada by Nazi Germany resulted in the displacement of local populations and the influx of foreign workers to meet wartime labour demands. Polish labourers, predominantly young and from economically disadvantaged regions like Ciechanów, were among those forcibly mobilized. They were subjected to harsh treatment, discriminatory laws, and often found themselves in precarious working and living conditions.The paper highlights the experiences of Polish labourers in various industries, including construction and agriculture, and examines the motivations behind their escapes from forced labour. It also addresses the sensitive issue of sexual violence against female Polish workers, which remains largely overlooked in historiography.The liberation of Klaipėda by Soviet forces in 1945 brought an end to forced labour in the region, but many labourers faced further hardships, including mistreatment by Soviet authorities. The paper concludes with reflections on the post-war reparations process and calls for further research and cross-border cooperation to fully understand the history of forced labour in the Klaipėda region and its lasting impact on affected communities.
Keywords: World War II; forced labour during World War II; polish labourer; gestapo; gestapo Zichenau / Schröttersburg; Klaipėda; Memelgebiet; Institute of National Remembrance